Coolaborative Governance dalam Pengembangan Desa Wisata : Studi Tentang Pengembangan Desa Wisata Bukit Porong di Desa Coal Kecamatan Kuwus Kabupaten Manggarai Barat - Fatima Wahyuni Kurnia; Frans B.R Humau; Diana S.A.N. Tabun (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study is motivated by the importance of developing tourism villages as an effort to promote local economic growth through stakeholder collaboration. Coal Village in West Manggarai Regency has developed Bukit Porong as a nature- and culture-based tourism destination involving the government, local communities, and private sectors. However, the collaboration process remains suboptimal due to limitations in infrastructure, human resources, and coordination. This study aims to examine the collaborative governance process in the development of Bukit Porong Tourism Village using the collaborative governance model proposed by Ansell and Gash (2007). A qualitative approach with a descriptive method was employed, using interviews, observations, and documentation as data collection techniques. The results show that collaborative governance has been implemented but has not yet reached optimal effectiveness, particularly in institutional arrangements, coordination mechanisms, and community participation. Despite these challenges, collaboration has contributed to increasing tourist visits and supporting local economic activities. The study concludes that collaborative governance is still in a transitional stage and requires strengthening institutional design, leadership capacity, and community involvement to ensure sustainable tourism development.